The Role of the Use of Low Molecular Weight Heparin in the Prevention of Deep Venous Thrombosis after Total Knee Arthroplasty - Jasim, Auday H.; Khudiar, Abdullah Y. (AL-Kindy College Medical Journal, 2011)
Background A prospective clinical study wasperformed to compare the efficacy of the use of lowmolecular-weight heparin group (enoxparin group)with control group in the prevention of deep-veinthrombosis after total knee arthroplasty.Aim of the study: to assess the prevalence of DVTafter total knee arthroplasty and evaluate theimportance of the use of low molecular weightheparin in the prevention of this DVT.Methods Thirty-three patients undergoing totalknee arthroplasty were randomly divided into twogroups. One group consisted of 12 patients whoreceived no prophylaxis with an anticoagulant (thecontrol group), other group consisted of 21 patientswho received the low-molecular-weight heparinenoxparin (enoxparin group) 4000 I.U. S.C 6 hoursafter surgery for two weeks after the operation thenaspirin 100 mg until 6th week after operation.Bilateral duplex ultrasonography was performedpreoperatively and at (5-7) days postoperatively.Results The prevalence of deep-vein thrombosiswas 58% in the control group, 38% in the enoxparingroup.Conclusions Enoxaparin significantly lowered theprevalence of deep-vein thrombosis after total kneearthroplasty.